Knowledge and Awareness about Burning Mouth Syndrome among Dental Students - Manju J; Mutum Sangeeta Devi; Meena.J; Rahul B; Kavitha.M; Niveditha.B (Indian Journal of Forensic Medicine & Toxicology, 2021)
Aim: This study was conducted to evaluate the knowledge and level of awareness about Burning mouth syndrome among dental students. Method: The study was carried out among the dental students.A self-constructed questionnaire was made and given to a total of 100 students. The answers were recorded and converted into numbers and percentages.Results: The results of the study reveal that undergraduate dental students have a fair knowledge about burning mouth syndrome.Conclusion: There is an increased need for comprehensive educational programmes and clinical exposure for students to be aware about burning mouth syndrome.